Analysis of the Role of Professional Teachers in Building Student Competencies in 21st Century Learning - Subarkah, Melani Damaiyati; Alrahmadani, Risa; Mardiyana, Sefa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
In the 21st century, the main focus is on the development of the industrial revolution 4.0 era which emphasizes the importance of knowledge. Learning in this era aims to create more job opportunities and expand employment for Indonesians with superior quality human resources. The role of professional teachers is crucial in creating effective learning to develop creative, communicative, critical thinking and collaboration skills for learners in this era. The purpose of this study is to evaluate the role of professional teachers in developing students' competencies in the 21st century lear ning era. This research is a literature study, which involves collecting materials from books and scientific journals. The results showed that young teachers have a significant role in improving students' ability to master 21st century skills. They need to have an understanding of 21st century skills and the ability to apply them in learning. In addition, they must also be able to provide guidance and prepare students to master these skills. From the results of this study, it can be concluded that training and implementation of 21st century learning for young teachers is very effective in improving students' ability to master 21st century skills. Keywords : Professional, Competence, 21st Century Learning